Highly Sensitive and selective glucose biosensing at carbon paste electrodes modified with electrogenerated magnetite nanoparticles and glucose oxidase - Comba, Fausto Nahuel (2010)
This work reports the advantages of carbon paste electrodes modified with electrogenerated magnetite nanoparticles. The nanoparticles present catalytic activity towards hydrogen peroxide reduction. The incorporation of glucose oxidase (GOx) and magnetite in a carbon paste matrix have made possible the development of an efficient glucose biosensor. The effect of the amount of GOx and magnetite present in the composite on the response of the biosensor was critically evaluated. The biosensors demonstrated to be highly selective, with negligible interference of ascorbic acid and uric acid. The proposed biosensor was challenged with human blood serum demonstrating an excellent correlation with the spectrophotometric method.